Management of Enamel Hypoplasia in Maxillary Incisors with Composite Direct Veneers: Case Report - Rafania Atikah, Ayu; Irwantoro, Edward; Widjiastuti, Ira (Conservative Dentistry Journal, 2022)
Background: Dental esthetics is an important aspect that needs to be considered in today's dental treatment planning. Enamel hypoplasia is teeth discoloration from yellowish to brownish due to disturbances during the amelogenesis process. Direct veneers are a conservative treatment option that supports the esthetics of anterior teeth. Purpose: To improve patient's appearance by a viable treatment option that offered rehabilitation of anterior teeth. Case: A 18-year-old female patient felt uncomfortable and wanted to improve her appearance because the front teeth had old fillings turned yellowish and white spots. Objective examination showed enamel hypoplasia in 12, 11, 21, 22 and secondary caries in 11 and 22. Case Management: The treatment plan was direct composite veneers. The initial stage is digital smile design analysis and composite shade selection using the button try technique. Minimally invasive preparations were performed on teeth 12, 11, 21, 22. Etching using 37% phosphoric acid and bonding agent was applied to the prepared enamel. The layering technique is used for composite applications. Finishing, contouring and polishing using Soflex Disc Coarse and Diacomp Twist. Conclusion: Direct composite veneers are a viable treatment option for patients requiring rehabilitation of anterior teeth.